The Interplay of Talent, Interest, and Teaching Competence: A SEM-PLS Analysis of Pre-Service Mathematics Teachers - Lestiana, Herani Tri; Pramesti, Santika Lya Diah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Based on Expectancy-Value Theory, talent and interest are often assumed to relate to individual competence. However, few studies have examined talent, interest, and competence simultaneously using SEM-PLS. This study analyzed the direct and indirect relationships among talent, interest, and the teaching competence of prospective mathematics teachers using SEM-PLS. The participants were 87 fifth-semester students in the Mathematics Education Department at UIN Siber Syekh Nurjati Cirebon. Data were collected through an interest questionnaire, a talent test, and teaching-competence observations. The results indicated that talent had a positive but non-significant effect on interest (coefficient = 0.487; p = 0.127) and on teaching competence (coefficient = 0.236; p = 0.531). Interest showed a negative but non-significant effect on teaching competence (coefficient = -0.243; p = 0.289). The mediation test also showed that interest did not significantly mediate the effect of talent on teaching competence (indirect coefficient = -0.118; p = 0.369). The explained variance was 0.237 for interest and 0.059 for competence, indicating that the model accounted for only a small proportion of variance. These findings suggest that teaching competence is more likely shaped through experience and social interaction in educational settings than as a direct outcome of talent or interest. The lack of significant relationships highlights the complexity of teaching-competence development. Practically, teacher education institutions should support talent and interest exploration while strengthening competence development through structured mentoring, early career exploration workshops, and systematic talent identification.